2020
DOI: 10.26434/chemrxiv.12751361.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In Silico Docking Analysis Revealed the Potential of Phytochemicals Present in Phyllanthus Amarus and Andrographis Paniculata, Used in Ayurveda Medicine in Inhibiting SARS-CoV-2

Abstract: No therapeutics and vaccines are available against SARS-CoV-2 at present. In the current study we have made an attempt to provide preliminary evidences for interaction of 35 phytochemicals from two plants (<i>Phyllanthus amarus </i>and <i>Andrographis paniculata</i> used in Ayurveda<i>)</i> with SARS-CoV-2 proteins (S protein, 3CLpro, PLpro and RdRp) through <i>in silico</i> docking analysis. The docking was performed with the aid of AutoDock Vina and ADME and ot… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…This is supported by the results of Sharma et al (2022) which showed that some of the main diterpenoid compounds of A. paniculata, including andrographolide and neoandrographolide, have no interaction with amino acid residues of the RdRp target protein. Although reported as having good binding affinity, isoandrographolide does not have hydrogen bonding with the amino residue RdRp (Hiremath et al, 2021).…”
Section: Rna-dependent Rna Polymerasementioning
confidence: 96%
See 1 more Smart Citation
“…This is supported by the results of Sharma et al (2022) which showed that some of the main diterpenoid compounds of A. paniculata, including andrographolide and neoandrographolide, have no interaction with amino acid residues of the RdRp target protein. Although reported as having good binding affinity, isoandrographolide does not have hydrogen bonding with the amino residue RdRp (Hiremath et al, 2021).…”
Section: Rna-dependent Rna Polymerasementioning
confidence: 96%
“…Neoandrographolide and isoandrographolide are the two compounds reported to mostly interact with RdRp. A study by Hiremath et al (2021) reported that neoandrographolide interacts with the active site of this protein through hydrogen bonds at four residues, namely, Ala125, Asp126, Arg132, and His133. This finding is supported by the results from Murugan et al's (2021) study, which suggested that neondrographolide is a compound with the potential as an inhibitor of RdRp even though its binding affinity value is greater than that of remdesivir drugs, which is due to the stability of its binding to the Asp336, Thr440, and Asp507 residues of the target protein.…”
Section: Rna-dependent Rna Polymerasementioning
confidence: 99%
“…In an in-silico docking analysis, Corilagin showed a high binding affinity at −9.30 kcal/mol towards the active site residues (ASN705, GLN724, HIS133, LEU207 and TYR129) of RdRp in SARS-CoV-2 via hydrogen bonding (Ref. 60 ). A study conducted by Li et al .…”
Section: The Potential Of Anti-cancer Drugs To Inhibit Rdrp In Sars-c...mentioning
confidence: 99%
“…Accompanied with an appealing docking score (−9.30 kcal/mol) in comparison with Remdesivir at –7.6 kcal/mol, Corilagin holds a vast potential for drug repositioning against the SARS-CoV-2 (Ref. 60 ).…”
Section: The Potential Of Anti-cancer Drugs To Inhibit Rdrp In Sars-c...mentioning
confidence: 99%